I Am/We Are: Exploring the Online Self-Avatar Relationship. (January 2021) - Procter, Lesley
Research into how online avatars are used has mostly concentrated on the agentic user controlling the passive avatar. With the proliferation, variety, and increasing uptake of online representations now available to individuals, however, we might more productively examine the relationship between what I call the avatar-persona and the user as one in which the avatar-persona also plays a part. Due to the affordances of parasociality and self-presence, a dialectic interaction develops between the user and the avatar as extended and extraordinary self. This dialectic enables the avatar-persona to express a certain degree of influence over the user in some circumstances. My discussion of these dynamics is illustrated from observations made during an extended participant observation in a multi-user virtual environment Second Life.